Brain plasticity and migraine transformation: fMRI evidences. (1st December 2016) - Lovati, Carlo; Giani, Luca; Mele, Francesco; Sinelli, Alessandro; Tien, Thien Trung; Preziosa, Giulia; Mariani, Claudio
ABSTRACT: Introduction : Chronification transforms episodic migraine into the pathologic chronic form. Biological characteristics of the migrainous brain progressively change, in predisposed subjects, under the repetition of external and internal stimuli. Modifications involve neurons, synapses, neurotransmitters, receptors, connectivity and pain control. f-MRI is a promising way to explore the still unclear biology of this progression. Areas covered : Data included were obtained from the most relevant and updated works available on PubMed about this topic. We summarized the pathophysiology of migraine chronification and of brain plasticity, and we described the different fMRI techniques and their main evidences about migraine transformation. Expert commentary : Functional-MRI has revealed many aspects regarding the peculiarity of the migrainous brain and its tendency toward chronicity but a series of questions are still open: What are the hallmarks of the predisposition to chronification? Which elements are the cause and which the consequence of this process?